Information Technologies in Medicine 5th International Conference, ITIB 2016 Kamień Śląski, Poland, June 20 - 22, 2016 Proceedings, Volume 1 - Piętka, Ewa; Badura, Pawel; Kawa, Jacek; Wieclawek, Wojciech (Advances in Intelligent Systems and Computing,, 2016)
ITiB'2016 is the 5th Conference on Information Technologies in Biomedicine organized by the Department of Informatics & Medical Equipment of Silesian University of Technology every other year. The Conference is under the auspices of the Committee on Biocybernetics and Biomedical Engineering of the Polish Academy of Sciences. The meeting has become a recognized event that helps to bridge the gap between methodological achievements in engineering and clinical requirements in medical diagnosis, therapy, and rehabilitation. Mathematical information analysis, computer applications together with medical equipment and instruments have become standard tools underpinning the current rapid progress with developing Computational Intelligence. Members of academic societies of technical and medical background present their research results and clinical implementations. This proceedings (divided in 2 volumes) include the following sections: Ø  Image Processing Ø  SignalProcessing Ø  Medical Information System & Database Ø  Ambient Assisted Living Ø  Bioinformatics Ø  Modeling & Simulation Ø  Biomechatronics Ø  Biomaterials.